Notes of the flora of serra Aracá - Julian A. Steyermark (Acta Amazonica, 1986)
A new species of Tepuianthus (Tepuianthaceae) is described from Serra Aracá in Amazonas, Brazil. Also discussed is the occurrence on this isolated tepui of two species of Perissocarpa (Ochnaceae). This is the first record of that genus in Brazil.